2015
DOI: 10.1159/000430300
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Preconditioning Promotes the Survival and Migration of Bone Marrow Stromal Cells

Abstract: Background: Preconditioning with the volatile anesthetic isoflurane exerts protective effects in animal models of ischemia. The cytoprotective effects of isoflurane are dependent on the expression of hypoxia inducible factor-1 (HIF-1), a dimeric transcription factor that mediates cellular responses to hypoxia. Methods: We investigated the effect of isoflurane preconditioning on bone marrow stromal cell (BMSC) survival and function. Results: Short exposures to low isoflurane concentrations promoted in vitro sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“… [ 91 ] ISO Bone marrow Stroke model In vitro / in vivo (rats) Upregulated CXCR4 and HIF-1α expression; improved engraftment into the ischemic brain and improved functional recovery. [ 92 ] CCPA Dental pulp Osteogenesis In vitro Improved proliferation and osteogenic differentiation; upregulated RUNX-2 and alkaline phosphatase expression; improved mineralization in extracellular matrix. [ 96 ] ATRA Bone marrow (rat) Excisional wounds model In vitro / in vivo (rats) Upregulated COX-2, HIF-1, CXCR4, CCR2, VEGF, Ang-2 and Ang-4 gene expression; improved wound healing.…”
Section: Msc Priming With Pharmacological or Chemical Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“… [ 91 ] ISO Bone marrow Stroke model In vitro / in vivo (rats) Upregulated CXCR4 and HIF-1α expression; improved engraftment into the ischemic brain and improved functional recovery. [ 92 ] CCPA Dental pulp Osteogenesis In vitro Improved proliferation and osteogenic differentiation; upregulated RUNX-2 and alkaline phosphatase expression; improved mineralization in extracellular matrix. [ 96 ] ATRA Bone marrow (rat) Excisional wounds model In vitro / in vivo (rats) Upregulated COX-2, HIF-1, CXCR4, CCR2, VEGF, Ang-2 and Ang-4 gene expression; improved wound healing.…”
Section: Msc Priming With Pharmacological or Chemical Agentsmentioning
confidence: 99%
“…In vitro preconditioning of BM-MSC with ISO (low doses and short treatment duration, 2% ISO for 4 h) increases cell viability and migration potential. There was hypoxia-induced upregulation of CXCR4 and HIF-1α, whereas no effect was observed in the expression of HIF-1β [ 92 ]. However, longer exposures to ISO at higher doses decreased MSC viability and migration potential.…”
Section: Msc Priming With Pharmacological or Chemical Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of BMSCs on improving neurological functions have been well studied in recent years and studies are ongoing into methods of increasing their viability after transplant [33,34]. BMSCs promote remyelination and accelerate conductive velocity of electrophysiology of demyelinated nerves [35].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) could differentiate into various cell types because they are multi-potent and have a self-renewing capacity [13]. A previous study demonstrated that BMSC transplantation is effective in acute brain injury by increasing neurotrophic factors and promoting functional recovery [14].…”
Section: Introductionmentioning
confidence: 99%